PERSEPSI GURU DAN SISWA MENGENAI MANAJEMEN KELAS PADA PROSES PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL - Hendra Saputra Wibowo; Afifah Siska Febriani, Eka Ulfah Nurjanah, Tri Yuni Pamungkas, Dhesta Youlandi Rahayu Sulistiyawati (CV. ADIBA ASIHA AMIRA, 2025)
This study aims to understand the perceptions of teachers and students of grade 6 of Tegalsari Elementary School regarding classroom management in technology-based learning processes. This study uses a mix method technique with a qualitative descriptive analysis approach with interviews and observations for 3 months and a quantitative approach using a Likert scale questionnaire to measure student perceptions. The subjects of the study consisted of homeroom teachers and all 13 grade 6 students. Data analysis from interviews and observations was carried out using the steps of Miles and Huberman, namely: data reduction, data presentation, and drawing conclusions. The data was processed using a triangulation test so that the data produced was credible and valid. The results of the study showed that teachers and students had the same perceptions regarding the effectiveness of technology-based classroom management applied during the learning process which can make it easier for teachers to create a conducive atmosphere, foster enthusiasm for learning, and students feel less bored so they can focus while learning. However, there are several obstacles to the limitations of digital media facilities owned by schools, such as chromebooks, projectors, signals, and power outages quite often occur. This study provides insight and motivation to elementary school teachers to involve digital technology in managing classes during the learning process